High-efficiency, flexible and large-area red/green/blue all-inorganic metal halide perovskite quantum wires-based light-emitting diodes - Yang Bryan Cao; Daquan Zhang; Qianpeng Zhang; Xiao Qiu; Yu Zhou; Swapnadeep Poddar; Yu Fu; Yudong Zhu; Jin-Feng Liao; Lei Shu; Beitao Ren; Yucheng Ding; et al. (Nature Communications, 2023)
Abstract Metal halide perovskites have shown great promise as a potential candidate for next-generation solid state lighting and display technologies. However, a generic organic ligand-free and antisolvent-free solution method to fabricate highly efficient full-color perovskite light-emitting diodes has not been realized. Herein, by utilizing porous alumina membranes with ultra-small pore size as templates, we have successfully fabricated crystalline all-inorganic perovskite quantum wire arrays with ultrahigh density and excellent uniformity, using a generic organic ligand-free and anti-solvent-free solution method. The quantum confinement effect, in conjunction with the high light out-coupling efficiency, results in high photoluminescence quantum yield for blue, sky-blue, green and pure-red perovskite quantum wires arrays. Consequently, blue, sky-blue, green and pure-red LED devices with spectrally stable electroluminescence have been successfully fabricated, demonstrating external quantum efficiencies of 12.41%, 16.49%, 26.09% and 9.97%, respectively, after introducing a dual-functional small molecule, which serves as surface passivation and hole transporting layer, and a halide vacancy healing agent.